Neurodevelopmental assessment after congenital cytomegalovirus infection. Issue 4 (April 1986) - Pearl, K N; Preece, P M; Ades, A; Peckham, C S
Abstract : The neurodevelopmental state of 41 children with congenital cytomegalovirus infection and their controls was assessed at 2 years using the Griffiths scale. The scores achieved by children with congenital cytomegalovirus but with no associated neurological abnormality (asymptomatic) were similar to those of the control children, whereas the mean score of the five children with congenital infection and neurological impairment (symptomatic) was significantly lower. This study, which has the statistical power to detect differences in developmental quotient as small as five points, gave no evidence that at 2 years cytomegalovirus infection was associated with mental retardation in the absence of other neurological impairment. Thus 90% of children with congenital cytomegalovirus infection at 2 years are neurologically and developmentally normal.